Pengaruh Computer Anxiety, Kondisi Yang Memfasilitasi, Konsekuensi Jangka Panjang Dan Faktor Sosial Terhadap Kinerja Individual Karyawan (Studi empiris pada Dinas Pendapatan dan Pengelolaan Kekayaan Aset Daerah di Kabupaten Karanganyar) - Sari, Erlinda Arum; , Fatchan Achyani SE. M.Si, DR (2014)
The purpose of this study was to examine the influence of computer anxiety, conditions that facilitate the long-term consequences, and social factors on the performance of individual employees Department of Revenue and the Regional Asset Wealth Management in Karanganyar. The sample in this study were employees of the Department of Revenue and Asset Wealth Management area using computers to accomplish tasks. Technical analysis of the data used in this research is to test the validity and reliability, the classical assumption test, multiple regression analysis, f-test, t-test and test of the coefficient of determination (R²). The results showed that: (1) social factors have a significant effect on the performance of individual employees, Because the questionnaire results showed that respondents feel the environment in which they work to support the work with the help of information technology; (2) the long-term consequences affect the performance of individual employees this allows the relationship between employees with information technology it is bustling used so that the respondents feel that the use of information technology will have a positive impact for the future; (3) the conditions that facilitate the effect is not significant likelihood of weak ties is because in terms of the conditions that facilitate the measurement of the lack of facilities that allow employees to export more on information technology; (4) computer anxiety effect is not significant it is likely influenced by culture conditions